Skype - lessons learned from a history of success and failure in mergers and acquisitions - regulatory approval and Cisco challenge - Huscava, Simon (2024)
The eventful acquisition history of Skype first gained attention in 2005 with eBay’s $2.6 billion takeover of the then-unprofitable VoIP technology company. eBay’s failed attempts to integrate the software into its bidding platform and an associated $1.4 billion write-down illuminated the importance of credibility of synergies in the context of Mergers & Acquisitions. A subsequent majority stake sale to private equity investors at a $2.75 billion valuation and two attempted public floats later, Microsoft announced the staggering $8.5 billion acquisition that led to speculations about merger motives and raised concerns around competitive dynamics and merger control.